2018
DOI: 10.1177/1029864918817805
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a rhythmic pulse on the heart rate: Little evidence for rhythmical ‘entrainment’ and ‘synchronization’

Abstract: In this study, we investigate the influence of musical tempo on the heart rate. Previous studies showed ambiguous results. Two effects are considered: first, an adaption of the heart rate frequency to the tempo of a musical stimulus (‘entrainment’) and second, the phase synchronization between the stimulus-onset and the R-waves in the ECG (‘synchronization’). A regulatory feedback loop was programmed, which constantly measured the actual heart rate. A simple Djembé-beat was used as a musical stimulus and coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
7
1
Order By: Relevance
“…In other words, musical rhythms aligned with neither audiences' breathing cycles nor their heartbeat cycles. Although this lack of phase synchrony was expected for heart rhythms [40][41][42] , this contrasts previous findings that breathing aligns with musical beats 38,39 . There are a few potential reasons for this discrepancy between results.…”
Section: Heartbeat and Breathing Cycles Do Not Rhythmically Align To ...contrasting
confidence: 99%
See 1 more Smart Citation
“…In other words, musical rhythms aligned with neither audiences' breathing cycles nor their heartbeat cycles. Although this lack of phase synchrony was expected for heart rhythms [40][41][42] , this contrasts previous findings that breathing aligns with musical beats 38,39 . There are a few potential reasons for this discrepancy between results.…”
Section: Heartbeat and Breathing Cycles Do Not Rhythmically Align To ...contrasting
confidence: 99%
“…In the phase domain, some research indicates that the alignments of breathing/heartbeats to external rhythms aid the processing of upcoming stimulus events 36,37 . In music, respiration has been shown to entrain to musical beats 38,39 , while heartbeats do not [40][41][42] . Thus, the current study aimed to further assess cardiorespiratory synchrony as an index of engagement in response to music performances in a concert audience.…”
Section: Introductionmentioning
confidence: 99%
“…SRPC of both heart and respiration cycles was not significant. This was expected for the heart rhythms, as previous work showed that the heartbeat does not align with external beats (Ellis & Thayer, 2010;Koelsch & Jäncke, 2015;Mütze et al, 2020). However, this was unexpected for respiration, as previous studies found that breathing aligns with musical beats (Etzel et al, 2006;Haas et al, 1986).…”
Section: Discussionmentioning
confidence: 59%
“…One way is to calculate the coherence between oscillatory responses and actual note onsets. Although studies have shown that respiration aligns to musical beats (Etzel et al, 2006;Haas et al, 1986), there is limited evidence that heartbeats do the same (Ellis & Thayer, 2010;Koelsch & Jäncke, 2015;Mütze et al, 2020). However, this former approach assumes that oscillatory responses can occur at the frequency range of a stimulus.…”
Section: Stimulus-response Phase Coherencementioning
confidence: 99%
See 1 more Smart Citation